2001
DOI: 10.1177/107424840100600404
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Fluvastatin in Heart Transplant Recipients Taking Cyclosporine A

Abstract: During the last decades, transplantation has become an established tool for the treatment of terminal organ failure. Beside immunological factors, hyperlipidemia is the main problem after heart transplantation, causing rapid transplant coronary artery disease (TxCAD) and poor long-term prognosis at the beginning of the transplantation. Heart transplant recipients are now effectively treated with lipid lowering substances, of which HMG-CoA-reductase inhibitors are the most potent. However, treatment with these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 33 publications
(77 reference statements)
2
41
0
Order By: Relevance
“…These studies suggest that we have covered a physiologically relevant range of fluvastatin. However, fluvastatin metabolism may be affected by concomitant therapies, especially substances competing with cytochrome enzymes, and, in such cases, fluvastatin levels may need to be monitored (43). Any reactions with other therapies (as they would appear in patients with CF) were not investigated in our work, as they would have been beyond the scope of the study.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that we have covered a physiologically relevant range of fluvastatin. However, fluvastatin metabolism may be affected by concomitant therapies, especially substances competing with cytochrome enzymes, and, in such cases, fluvastatin levels may need to be monitored (43). Any reactions with other therapies (as they would appear in patients with CF) were not investigated in our work, as they would have been beyond the scope of the study.…”
Section: Discussionmentioning
confidence: 99%
“…10 It has been reported that the maximum blood concentration of FLV after 40 mg/day being administered orally for 4 weeks is approximately 0.6 mol/L. 26 This concentration is rather low for the inhibition of HCV replication in vivo, because the IC 90 of FLV was assigned as 6.7 mol/L in our assay system (Fig. 5B).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these immunosuppressants themselves could alter the bioavailability of many concomitantly given drugs and thus cause potentially important drug interactions. One of the most striking examples is the increased risk for rhabdomyolysis observed with the combination of CsA and statins (10,11). In clinical oncology, attempts have been made to increase the efficacy of anticancer agents by utilizing the inhibitory effect of CsA on PGP, albeit with variable success (12,13).…”
Section: Introductionmentioning
confidence: 99%